Structural, opto-electronic characteristics and second harmonic generation of solution processed CH3NH3PbI3-xClx thin film prepared by spray pyrolysis - Tanveer Karim, A.M.M.; Khan, M.K.R.; Hossain, M.S.; Kamruzzaman, M.; Azizar Rahman, M.; Mozibur Rahman, M. (Materials science & engineering. B, Solid-state materials for advanced technology, 2020)
[Display omitted] •Nanorods like crystalline CH3NH3PbI3-xClx thin film at an ambient atmosphere by spray deposition.•High absorption coefficient with a band gap of 1.64 eV.•Structural phase transition from tetragonal (at RT) to orthorhombic (at 80 K).•Generation of second harmonic emission. Nanorod like crystalline CH3NH3PbI3-xClx thin film was prepared by spray pyrolysis at an ambient atmosphere. X-ray diffraction (XRD) and Raman studies reveal the tetragonal perovskite phase of spray deposited film. The optical band gap of CH3NH3PbI3-xClx is estimated to ~1.64 eV which is consistent with vacuum based deposited perovskites. The CH3NH3PbI3-xClx film exhibits a high absorption coefficient of the order of 106 m−1. Photoluminescence (PL) study suggests that band-to-band radiative recombination occurs in CH3NH3PbI3-xClx film. Cathodoluminescence study confirms the emission of 1.67 eV at 80 K and 1.80 eV at 300 K. In this study, the second harmonic generation at photon energy 3.6 eV is reported for the first time at room temperature (RT). It is noted that the band edge peak position at 1.67 eV is being diffused and shifted to 1.80 eV at RT while the second harmonic peak position at 3.6 eV remains unchanged.